PENERAPAN INDEKS GINI UNTUK MENGINDENTIFIKASI TINGKAT PEMERATAAN PENDAPATAN DAN PENGELUARAN RUMAH TANGGA PEDESAAN DI WILAYAH JAWA DAN BALI - MADE OKA ADNYANA; RITA NUR SUHAETI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2003)
Gini Index application to identify rural income and expenditure distributions in Java and BaliAreas. Rural household welfare can be approached by evaluating income ad expenditure levelboth for total and capita level. In the mean time, income structure reflects activity distributionas sources of income gained by the households. Income distribution level can be identified byapplying Gini Index. This study was conducted in various agro-ecosystems in Java and Bali.This paper discusses about income and expenditure structures of those rural households at thementioned agro-ecosystems. This study results was expected to be useful for research andassessment (R&A) in those areas mainly in evaluating outcome and impact of the R&A inthose respective agro-ecosystems.